2018
DOI: 10.1016/j.lithos.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Portrait of a giant deep-seated magmatic conduit system: The Seiland Igneous Province

Abstract: The Seiland Igneous Province (SIP), Northern Norway, contains >5000 km 2 of mafic, ultramafic intrusions with minor alkaline, carbonatite and felsic rocks that were intruded into the lower continental crust at a depth of 25 to as much as 35 km.The SIP can be geochemically and temporally correlated to numerous dyke swarms throughout Scandinavia at 560-610 Ma, and is linked to magmatic provinces in W-Greenland and NE-America that are collectively known as the Central Iapetus Magmatic Province (CIMP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 54 publications
3
76
0
Order By: Relevance
“…Previous authors have reported local serpentinization in surface exposures of the ultramafic rocks (Emblin, ; Grant et al, ; Larsen et al, ). However, there is one area of pervasive serpentinization of the CS dunites, which is associated with a fault trending east‐west at 70°07′N that crosscuts all formations (Figure ), here termed the Storvannet fault.…”
Section: Geologymentioning
confidence: 95%
See 4 more Smart Citations
“…Previous authors have reported local serpentinization in surface exposures of the ultramafic rocks (Emblin, ; Grant et al, ; Larsen et al, ). However, there is one area of pervasive serpentinization of the CS dunites, which is associated with a fault trending east‐west at 70°07′N that crosscuts all formations (Figure ), here termed the Storvannet fault.…”
Section: Geologymentioning
confidence: 95%
“…The ULS has cyclic units consisting of a dunitic cumulate layer (Fo 85.1–77.4 ; Emblin, ) that gradually taper into wehrlitic cumulates. The later intrusion of the CS into the wehrlitic cumulates led to the assimilation of large volumes of the ULS under the formation of replacive dunites (Larsen et al, ). More than 50% of the surface outcrop of the RUC is CS, which consists of olivine cumulates (>90%) with less than 10% clinopyroxene.…”
Section: Geologymentioning
confidence: 99%
See 3 more Smart Citations